A study of Chinese consumers' adoption behaviour toward virtual fitting rooms. Issue 2 (3rd May 2020) - Li, Ailin; Xu, Yingjiao
ABSTRACT: The purpose of this study was to investigate Chinese consumers' adoption behaviour toward VFRs by using the Technology Acceptance Model. Additionally, this study aimed to examine the influence of two relevant personality traits, fashion leadership and technology anxiety, on consumers' VFRs adoption. Data were collected from 474 Chinese consumers via an online survey. Comparative analyses and regression analyses were conducted to test the proposed conceptual model regarding Chinese consumers' adoption intention towards VFRs. It was surprising to learn that perceived usefulness, among the three perceptions suggested by TAM, had the relatively least influence on Chinese consumers' adoption intention toward VFRs. Additionally, moderating effects of fashion leadership and technology anxiety were found on the relationship between consumers' perceptions and adoption intention toward VFRs. The findings could provide implications to retailers and brands in their endeavours to motivate and encourage different consumers to use VFRs for online apparel shopping.